Prevalence and Phylogenetic Analysis of Lipoprotein-Gene ragB-1 of Porphyromonas gingivalis-A Pilot Study - Sarah Böcher; Hendrik L. Meyer; Evdokia Dafni; Georg Conrads (MDPI AG, 2023)
Porphyromonas gingivalis (P.g.) is a key pathogen involved in periodontal diseases. The aim of this study was to investigate the prevalence and phylogenetic origin of the lipoprotein-gene ragB in its most virulent variant, ragB-1 (co-transcribed with ragA-1 as locus rag-1), in different P.g. strains collected worldwide. A total of 138 P.g. strains were analyzed for the presence of ragB-1 by pooled analysis and subsequently individual PCRs. Sequencing a core fragment of ragB-1 of the individual strains made it possible to carry out a phylogenetic classification using sequence alignment. In total, 22 of the 138 P.g. strains tested positive for ragB-1, corresponding to a prevalence of 16%. The fragment investigated was highly conserved, with variations in the base sequence detected in only three strains (OMI 1072, OMI 1081, and OMI 1074). In two strains, namely OMI 1072 (original name: I-433) and OMI 1081 (original name: I-372), which originate from monkeys, two amino-acid alterations were apparent. Since ragB-1 has also been found in animal strains, it may be concluded that rag-1 was transferred from animals to humans and that this originally virulent variant was weakened by mutations over time so that new, less virulent, adapted commensal versions of rag (rag-2, -3, and -4), with P.g. as the host, evolved.